The Influence of Social Media Marketing Sociolla on Brand Loyalty Through Brand Trust and Brand Equity - Fidia Shabrina; Agus Abdurrahman (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to identify the influence of social media marketing on brand loyalty through brand trust and brand equity. By using a quantitative approach through the distribution of online questionnaires and obtained a number of 152 respondents. The number of respondents was obtained based on the criteria of respondents who have social media, aged 18 - 40 years and know about Sociolla. Data analysis using the PLS-SEM method. The results of this study indicate that social media marketing has a positive influence on brand trust, brand equity and brand loyalty. Brand trust has a positive effect on brand equity but does not have a positive impact on brand loyalty. Brand equity has a positive influence on brand loyalty. This research can be used as an additional reference for further research involving social media marketing, brand trust, brand equity, and brand loyalty. As for the company, this research can be a consideration in improving communication and service to Sociolla consumers in order to increase brand loyalty.